A influência de paliteiros estruturando assembléias de peixes em reservatórios : dois estudos de caso na América do Sul. - Gois, Karen Silvério (2011)
The importance of subaquatic structures in determining fish assemblages is largely recognized in the literature. However, most of the studies are focused in aquatic macrophytes, and studies dealing with the influence of submersed trunks, resulted from the formation of reservoirs without the removal of the arboreal vegetation, are scarce. It is expected that submerged vegetation augment the biogenic capacity of reservoirs, increase the structural habitat complexity, contributing to the maintenance of a more diverse fish assemblage. In addition, submersed dead trees may be colonized as preferential habitats for some species. It is equally expected that, with the process of decomposition and the subsequent reduction in complexity, part of the function is lost. This study has as purpose to evaluate these predictions by comparing the abundance and composition of fish assemblages in habitats with and without submerged arboreal vegetation in two reservoirs with distinct ages (Itaipu, up to five year after its formation; Mourão, 30 years after its formation). Results showed the importance of the structured areas (with submerged vegetation) for the abundance of fish in both reservoirs. However, their role in maintaining species richness and diversity was significant only during the first years after the impoundment, when these environments also harbor a greater variety of characteristic (indicator) species. The occupation of these habitats by small sized species with an invertivorous diet indicates that the non removal of the arboreal vegetation contributes to increase the biogenic capacity of reservoirs, leading to greater productivity, in addition to provide shelter against predation. Under the perspective of conservation of fishery resources we concluded that the decisions related to the fate of arboreal vegetation in new reservoirs should never consider its total removal. It should be considered only the removal of what is necessary to maintain acceptable water quality, even with transitory and localized hypoxia processes.